Epstein–Barr virus‐positive plasmacytoma in immunocompetent patients. Issue 2 (19th February 2015) - Loghavi, Sanam; Khoury, Joseph D; Medeiros, L Jeffrey
<x xml:space="preserve">Abstract</x> Aims Extramedullary plasmacytomas are often localized, clinically indolent neoplasms, and affected patients usually respond to radiation therapy or limited cycles of chemotherapy. In contrast, plasmablastic lymphomas are clinically aggressive neoplasms composed of immunoblastic or plasmablastic cells and associated with more mature plasma cells in some cases. Patients with plasmablastic lymphoma usually have a poor prognosis despite aggressive chemotherapy. Evidence of Epstein–Barr virus (EBV) infection is uncommon in plasmacytoma, but common in plasmablastic lymphoma, and is therefore helpful in differential diagnosis. The aim of this study is to describe four cases of plasmacytoma arising in immunocompetent individuals that were diffusely positive for Epstein–Barr virus‐encoded small RNA as shown by in‐situ hybridization. Methods and results We describe the clinicopathological and immunophenotypic findings of four EBV‐positive plasmacytomas arising in immunocompetent patients. These tumours were characterized by diffuse proliferation of mature‐appearing plasma cells intermixed with a briskly reactive, CD8‐positive, TIA‐1‐positive cytotoxic T‐cell infiltrate. Long‐term follow‐up was available for all patients, and all were alive and free of disease at last follow‐up (median 43.4 months). Conclusions We suggest the term EBV‐positive plasmacytoma in immunocompetent patients for these lesions. It is essential to distinguish these tumours from plasmablastic lymphoma, as the latter diagnosis is associated with a much poorer prog‐nosis, and patients require much more aggressive therapy.